THE INFLUENCE OF WORK DISCIPLINE AND WORKLOAD ON EMPLOYEE PERFORMANCE (Study on Community Empowerment for Helath Service Employees At California District) - John Zysman; Arnaud Costinot (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
This study aims to determine"The Influence of Work Discipline and Workload on Employee Performance(Study on Community Empowerment for Helath Service Employees). The results of this study indicate that 1) it can be seen that tcount (1,959) < ttable (2.045), likewise with a significance value of 0,060> 0.05 it can be concluded hypothesisfirst denied, meaningWork Discipline Variable (X1) has no significant effect on Employee Performance Variable (Y). 2)it can be seen that tcount (1.023) < ttable (2.045), and a significance value of 0.315 > 0.05, it can be concluded that the second hypothesis is rejected, meaningWorkload Variable (X2) has no positive and significant effecton Employee Performance Variables (Y) .3) it can be seen that Fcount (10.247) > Ftable (3.34), and a significance value of 0,000<0.05, it can be concluded that the fourth hypothesis is accepted, meaningWork Discipline Variable (X1), Workload Variable (X2), have a significant simultaneous effect on Employee Performance Variable (Y).